PENINGKATAN KETERAMPILAN BERBICARA PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN ROLE PLAYING DI KELAS IV SDS IT LUQMAN KOTA PADANG - Nofita, Diandra; Sukma, Elfia; Yenti, Yesni; Muhammadi, Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low speaking skills of fourth-grade students at Luqman Islamic Elementary School in Padang City, particularly in interview texts. This problem is caused by a learning process that still focuses on theoretical delivery, a lack of practical opportunities for students, and low self-confidence. This study aims to assess the improvement of students' speaking skills through the application of the role-playing learning model. This study used Classroom Action Research (CAR) with qualitative and quantitative approaches, conducted in two cycles, involving 22 students as subjects. Data collection techniques included observation, interviews, and speaking skills tests. The results showed improvements in lesson planning and implementation, as well as student speaking skills. The average speaking skill increased from 69.3% in the first meeting of cycle I (poor category), to 76.4% in the second meeting of cycle I (sufficient category), and reached 84.1% in the second cycle (good category). Furthermore, teacher and student activity also increased, reaching the excellent category. Therefore, it can be concluded that the application of the role-playing learning model is effective in improving students' speaking skills in interview text learning in elementary schools.